PENGENALAN MANAJEMEN BISNIS SYARIAH MELALUI PELATIHAN KEWIRAUSAHAAN PEMBUDIDAYAAN DAN PEMASARAN IKAN HIAS DI DESA CIBUNIAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Dede Ririz; Tubagus Rifqy Thantawi; Bayu Purnama Putra (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract Entrepreneurship and Marketing Training for Ornamental Fish Cultivation in Pamijahan Village as a form of dedication to independence and existence in the community. This service activity aims to provide assistance to Betta fish cultivators, and this training is in collaboration with the Betta Community in Pamijahan District to build a betta fish cultivation and marketing business (Betta sp.). This activity is carried out through the stages of introducing the potential for ornamental fish cultivation, building relationships with ornamental fish cultivators and marketers, and developing promotional strategies in business pioneering, marketing, and alumni business development. This mentoring activity resulted in a pioneering business for the cultivation and marketing of ornamental fish, especially betta fish with the name Exotic Betta. The business that was initiated within three months has shown business prospects with an increase in sales and expansion of marketing areas, both in Pamijahan Village and regencies to areas outside Java Island. Promotion and marketing of Exotic Betta betta fish through online media and social media has made this business unit quickly recognized by betta fish hobbyists. Business development needs to be done by diversifying commodities to increase and develop ornamental fish marketing business. Keywords: alumni, entrepreneurship, betta fish, community service